ANALISIS POTENSI LIKUIFAKSI PADA PASIR VULKANIK DI PANTAI GLAGAH KULONPROGO BERDASARKAN DATA N-SPT - Hanindya Kusuma Artati; Widodo Pawirodikromo; Edy Purwanto (TEKNISIA, 2020)
One of the most causes of damage to structures during earthquake is a liquefaction. Liquefaction happened in a loose sand which saturated under earthquake shaking.  Earthquake shaking will cause cyclic loading to the surface of the ground which potential for occurrence of liquefaction. The liquefaction phenomenon is a soil behavior under cyclic loads that occurs in just a few moments. Due to the short cyclic load, the soil mass suddenly changes from a solid limit to a liquid limit or has a main consistency such as liquid. Liquefaction events during an earthquake can be characterized by the presence of ground movement in the horizontal direction, seepage water out from fracture of the ground, movement of sloping or descending buildings, displacement of ground advance, and landslides. This study took a case study in Glagah Beach at Kulonprogo Regency. That is beach areas which is a landform alongside a body water which consist of loose particles such as sand where Yogyakarta International Airport (YIA) is located. Analysis was carried out to determine the potential of liquefaction based N-SPT data using the Seed, Martin & Lysmer (1975).  Based on these data, The Cyclic Stress Ratio (CSR) value is calculated, which is the ratio between the average shear stress caused by the earthquake with the effective vertical stress in each layer and the value of the Cyclic Resistance Ratio (CRR), which is the amount of soil resistance to liquefaction. The analysis in the Kulonprogo Regency area is an area that is considered to require liquefaction. Analysis of liquefaction potential based on on N-SPT data with the Seed, Martin & Lysmer (1975) method on a 6,3 magnitude earthquake. The Result indicate the potential for liquefaction occurs up to a depth of 8,5 meters.